SUPPORT AND FAMILY PERCEPTION ABOUT QUALITY OF PATIENTS LIFE WITH MENTAL DISORDERS - Irfan Irfan; heriyati heriyati; Saharani Saharani (Media Kesehatan Politeknik Kesehatan Makassar, 2020)
Mental disorders are thought patterns that are usually associated with problems or distorted problems in one or more important functions for humans, namely psychological, behavioral, biological, and change functions not only in the relationships of these people but also in society. The purpose of this study is to discuss family relationships with family perceptions about the quality of life of patients with mental disorders. The research design used was analytic description with cross-sectional study, sample selection with purposive sampling technique, the number of samples found was 64 samples. Data were analyzed using chi-square test. Statistical test results obtained about family relations with a quiet family about the quality of life of patients for p = 0,000 <0.05. The conclusion of this study is about the relationship between family support and patients' perceptions about the quality of life of patients with mental disorders. Related to health care recommendations to provide maximum psychiatric care for patients, not only with care but also with useful information both from the medical and family and those around him to improve the quality of life of patients, such as socializing about caring for people with mental assistance and providing training for the cadres mostly about the care of patients with mental disorders.Keywords : family support, quality of life, mental disorder